Securing anonymous authenticated announcement protocol for group signature in internet of vehicle / Nur Afiqah Suzelan Amir - Nur Afiqah , Suzelan Amir (2021)
The past decade has witnessed a growing interest in vehicular networking and its vast array of potential applications. Improved wireless internet connectivity from vehicles has prompted road safety technologies to emerge. Announcement protocol in Internet of Vehicles (IoV) is an intelligent application to improve road safety, relieve traffic congestion and enhance the comfort of transportation. IoV has drawn extensive attention to provide more enjoyable and safer driving environment. It requires communication between vehicles, roadside units and pedestrian to disseminate safety related messages. Vehicular cloud (VC) computing can guarantee reliable and timely broadcast of safety messages. The integration of IoV and VC may significantly reduce road casualities. However, as vehicles are connected to the internet, it makes them accessible globally to a potential adversary or malicious parties. Safety-related application requires a message to be reliable, however it may intrude the privacy of a vehicle. Contrarily, if some misbehaviour emerges, the trusted party (TP) must be able to trace and revoke their legitimacy from the network. This is a contradiction between privacy and accountability since the privacy of a user should be preserved. We begin by analysing some existing announcement protocol based on various cryptographic primitives in the literature for VC and IoV respectively and consider to what extent they achieve the conflicting security requirements of reliability, privacy and accountability. From our analysis, we discover that there is no group signature technique has been proposed in the literature. This highlights the need to design a secure and efficient announcement protocol based on group signature technique in IoV technology. We formulate a generic abstraction of an announcement protocol for group signature. This generic abstraction aims to provide a basis for future construction of announcement protocol using group signature in IoV. To the best of our knowledge, our work is the first comprehensive construction of an announcement protocol in IoV that deploys group signature. We then analyse the security of our proposed protocol and evaluate its performance. We demonstrate that our protocol efficiently solves these conflicting security requirements of message reliability, privacy and accountability using 5G communication channel. The performance of our protocol is validated by simulations. The performance analysis and simulation results signify our work achieves performance efficiency in IoV communication.